(untitled) (Mongolian Journal of Geography and Geoecology, 2025)
Environmental protection infrastructure (EPI) within urbanized areas represents a vital component of ecological infrastructure and the contemporary economic urban framework. Its primary structural elements include enterprises and organizations dedicated to: a) the removal, storage, and burial of municipal solid and liquid waste; and b) the collection and processing of the recyclable portion of municipal waste (secondary material resources - SMR). The functioning of environmental protection infrastructure contributes to the recycling of municipal solid waste (paper, secondary polymer materials, secondary textiles, glass, and others) into secondary raw materials. The main goal of EPI is to reduce the environmental impact of waste generated by urban activities on both the surrounding environment and human health. The study area is the city of Irkutsk and its surroundings. Additionally, the operation of this infrastructure plays an important role in incorporating urban secondary raw materials into the economic cycle. The article is based on program and strategic developments involving the author, the results of expeditionary studies on the morphological composition of municipal solid waste, and similar studies and surveys. The methods used in the article include comparative geography, structuring, fieldwork, mapping, questionnaires, and others. The article is based on program and strategic developments involving the author, the results of expeditionary studies on the morphological composition of municipal solid waste, and similar studies.